How Do Financials Fundamentals Shape Firm? Evidence on the Mediating Role of Profitability - Purbasari, Intan (Eastasouth Institute, 2025)
This study examines the influence of capital structure, sales growth, and firm size on firm value, with profitability acting as a mediating variable. The empirical analysis is conducted on firms operating in the metals and related sub-sectors listed on the Indonesia Stock Exchange (IDX) over the period 2011–2021, with a sample comprising only firms with complete financial disclosures. Utilizing a causal-comparative research design, the study seeks to identify and generalize the structural relationships among key financial variables. The study considers capital structure, sales growth, and firm size as independent variables, with firm value serving as the dependent variable and profitability (as measured by Return on Assets) functioning as a mediating construct. A quota sampling technique was employed to select 14 firms from the metals and related sub-sectors listed on the Indonesia Stock Exchange (IDX), based on data completeness and sectoral relevance. The analytical framework incorporates descriptive statistics, classical assumption testing, model fit evaluation, multiple linear regression analysis, and hypothesis testing to examine the proposed relationships. The empirical results indicate that capital structure has a positive and statistically significant effect on firm value. Conversely, sales growth exhibits a negative but statistically insignificant relationship with firm value, while firm size demonstrates a significant negative impact. Profitability shows a positive and significant influence on firm value. Further analysis reveals that capital structure negatively affects profitability, although the effect is not statistically significant. Sales growth has a positive and significant impact on profitability, whereas firm size is positively related to profitability, albeit insignificantly. Mediation testing confirms that profitability does not mediate the relationship between capital structure and firm value; however, it significantly mediates the effects of both sales growth and firm size on firm value.